2013
DOI: 10.1146/annurev-arplant-042811-105534
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Views of Pectin Biosynthesis

Abstract: Recent progress in the identification and characterization of pectin biosynthetic proteins and the discovery of pectin domain-containing proteoglycans are changing our view of how pectin, the most complex family of plant cell wall polysaccharides, is synthesized. The functional confirmation of four types of pectin biosynthetic glycosyltransferases, the identification of multiple putative pectin glycosyl- and methyltransferases, and the characteristics of the GAUT1:GAUT7 homogalacturonan biosynthetic complex wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
387
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 498 publications
(408 citation statements)
references
References 180 publications
8
387
0
13
Order By: Relevance
“…b-1,4-galactan is a structural element found in the side chains of RG-I that in turn is a substructure of the complex multidomain pectic polysaccharides that have abundant HG domains (Atmodjo et al, 2013). A b-1,6-galactosyl substitution of b-1,4-galactan structures is rare in pectic side chains of RG-I (Arifkhodzhaev 2000;Ridley et al, 2001) but has been identified in extracts of garlic bulbs (Das and Das, 1977).…”
Section: Monoclonal Antibody Lm26 Binds Specifically To Phloem Sieve mentioning
confidence: 99%
See 1 more Smart Citation
“…b-1,4-galactan is a structural element found in the side chains of RG-I that in turn is a substructure of the complex multidomain pectic polysaccharides that have abundant HG domains (Atmodjo et al, 2013). A b-1,6-galactosyl substitution of b-1,4-galactan structures is rare in pectic side chains of RG-I (Arifkhodzhaev 2000;Ridley et al, 2001) but has been identified in extracts of garlic bulbs (Das and Das, 1977).…”
Section: Monoclonal Antibody Lm26 Binds Specifically To Phloem Sieve mentioning
confidence: 99%
“…Pectic polysaccharides are a major group of matrix polysaccharides, defined as galacturonic-acid-rich polymers, which comprise at least three major domains (Caffall and Mohnen 2009;Atmodjo et al, 2013). Homogalacturonan (HG) can be variably methyl-esterified and acetylated, and these modifications influence its interactions and supramolecular properties (Wolf et al, 2009).…”
mentioning
confidence: 99%
“…The most important seems to be the regulation of cell adhesion [110,111], which is essential for the development and functioning of multicellular organisms, as land plants. Pectins participate also in the apical and diffusive growth of cells [112], are involved in the defense response against pathogens [113] and regulate the cell wall strengthening [114]. In seed plants, three main groups of pectins are distinguished: homogalacturonan (HG), rhamnogalacturonan I (RG-I) and rhamnogalacturonan II (RG-II) [113].…”
Section: Pectins -Important Polysaccharides Of the Primary Cell Wallmentioning
confidence: 99%
“…Pectins participate also in the apical and diffusive growth of cells [112], are involved in the defense response against pathogens [113] and regulate the cell wall strengthening [114]. In seed plants, three main groups of pectins are distinguished: homogalacturonan (HG), rhamnogalacturonan I (RG-I) and rhamnogalacturonan II (RG-II) [113]. Sometimes, as the fourth separate group, the xylogalacturonans (XGA) are also given [112,115].…”
Section: Pectins -Important Polysaccharides Of the Primary Cell Wallmentioning
confidence: 99%
See 1 more Smart Citation